Toxicity Testing of Turi Putih Bark Extract on Mice Liver: Pengujian Toksisitas Ekstrak Kulit Batang Turi Putih pada Hati Mencit - Mujemilatul Hasanah; Jamilatur Rohmah (Academia Open, 2023)
General background the use of natural extracts in assessing toxicity has gained attention due to the growing interest in alternative medicine and natural products. Specific background Sesbania grandiflora, commonly known as turi putih, is a plant with potential medicinal properties, but its safety profile regarding hepatic toxicity remains inadequately explored. Knowledge gap while previous studies have examined various plants for their pharmacological effects, research specifically focusing on the hepatotoxicity of turi putih extract is lacking. Aims this study aims to evaluate the toxicity of ethanol extract from the bark of Sesbania grandiflora on liver function, as measured by SGOT and SGPT levels, in Mus musculus. Results showed no mortality or toxic symptoms in the mice exposed to the extract. Macroscopic examination of the liver indicated normal color, consistency, and shape. Statistical analysis yielded p-values of 0.502 for liver weight, 0.226 for SGOT, and 0.366 for SGPT, indicating no significant effects from the treatment. Novelty this research contributes new insights into the safety profile of Sesbania grandiflora, demonstrating its non-toxic effects at the tested doses. Implications the findings suggest that the bark extract of turi putih may be safe for use, highlighting its potential in herbal medicine without adverse hepatic effects. Highlights: No observed toxicity or mortality in mice after exposure to the extract. Normal liver function indicated by SGOT and SGPT levels. Potential safety of turi putih bark extract for medicinal use. Keywords: Turi Putih, Hepatotoxicity, Sesbania grandiflora, Mice, Ethanol Extract